Isolated Singularities of Solutions of Quasilinear Anisotropic Elliptic Equations - Namlyeyeva, Yuliya V.; Shishkov, Andrey E.; Skrypnik, Igor I. (Advanced nonlinear studies, 2006)
We consider a wide class of degenerate quasilinear second order elliptic equations with model representative , whose solutions have singularity at a point. There are established sharp point-wise conditions for removable isolated singularity of solutions of such equations. For solutions with non-removable point singularity (source type or fundamental solution), precise upper and lower estimates near the singularity point are obtained.